Features of a migration region – an analysis using the example of the Opolskie Voivodship - Heffner Krystian; Solga Brygida (Bulletin of Geography. Socio-Economic Series, 2013)
The authors of the article develop the concept of a migration region. The experiences of the Opolskie Voivodship in the sphere of external migration function as a field of reference. The issues connected with the factors preconditioning the formation of such a region are of utmost interest to the authors.